The Brahmin religion in India in travel books and geography from the third century AH until the end of the eighth century AH - Nashmi Jiyad Al-Alawi, Ahmed (Journal of College of Education, 2022)
ABSTRACTDespite the plurality of religions in the country of India, the Brahmin religion has taken a wide range among those religions in Indian society. In spite of also the beliefs and worships brought by that religion that did not exist before in their ancient religion, many of the Indian society embraced those beliefs. And it became at the top of the pyramid of the Indian religions due to the large number of its adherents, and it is still today. It also had a great influence on aspects of Indian life, including social, economic, cultural and military ones, and developed laws and legislations for it, as well as dividing society into groups and making each of them its own work through a set of legislative texts that were placed in their sacred book, the Vedas. This religion has spread to the neighboring countries of India and has become one of the religions with many followers
Keywords: Brahmin religion, worship and belief, India